13PHD1 deficiency promotes an atheroprotective metabolic phenotype. (15th July 2014) - Marsch, E; Demandt, J; Theelen, T; Gijbels, MJ; Rensen, PCN; Carmeliet, P; Fisher, EA; Biessen, EAL; Daemen, MJAP; Sluimer, JC
Abstract: Knockout of the oxygen-sensor HIF prolyl hydroxylase 1 (PHD1) was shown to switch metabolism towards glycolysis and reduced cellular oxygen consumption. As we recently showed a pro-atherosclerotic effect of plaque hypoxia, we hypothesised that reduced cellular oxygen consumption in PHD1 knockout mice alleviates atherosclerosis development. Low density lipoprotein receptor knockout (LDLr-/-, control) and LDLr-/-PHD1-/- mice (n=17 and 10, respectively) were placed on a western-type diet (WTD, 0.25 % cholesterol) for 8 weeks to induce atherosclerosis. Mice were injected with pimonidazole (100 mg/kg i.p.) prior to sacrifice to detect hypoxia in atherosclerotic plaques. Atherogenesis was attenuated in PHD1-/- mice, as shown by reduced aortic root plaque size (-35%, p=0.008, H&E) and necrotic core content (-38%, p=0.004, H&E). Plaque hypoxia was significantly reduced in PHD1-/- mice (-32%, p=0.02), despite unchanged MAC3 macrophage content, suggestive of reduced macrophage oxygen consumption. PHD1 deficiency led to significantly lowered plasma cholesterol (-21%, p<0.001) and triglyceride (TG) levels (-22%, p<0.001), as well as adipocyte size (-17% cell surface area, p=0.02, H&E), despite unchanged food intake. Hepatic cholesterol and TG re-entry in the circulation was similar in LDLr-/-PHD1-/- and control (n=6/group, WTD for 3 weeks), as studied after i.v. Triton WR1339 administration (500mg/kg). Also, hepatic cholesterol and TG content (μg lipid/mg protein) were unchanged in the atherosclerosis study, while liver weight decreased (-12%, p=0.004), suggesting that hepatic lipid synthesis is not affected by PHD1. In addition to impacting lipid metabolism, PHD1 deficient mice presented with relative leukopenia. Flow cytometry of whole blood showed reduced leucocyte count in PHD1-/- (-39% CD45+ leucocytes, p=0.001), affecting all leucocyte subsets, including Ly6C-high monocytes (-62%, p=0.03). It remains to be established, whether the leukopenia is a normalisation of WTD-induced hyper-inflammation or repression of leucocytes. Functionally, however, bone marrow-derived PHD1-/- macrophages were more resistant to ER stress-induced apoptosis (7-ketocholesterol, -50% TUNEL/total cell count, p<0.0001) and had improved efferocytosis capacity in vitro compared to control (+70%, p=0.03), which may have underlain the observed reduction in necrotic core formation. In conclusion, PHD1 deficiency promoted an atheroprotective metabolic phenotype, by improving lipid metabolism and macrophage phagocytosis and reducing inflammation, potentially pointing towards hitherto overlooked regulators of lipid metabolism.